Revealing the Role of Earnings Management and Leverage in the CSR-Financial Performance Nexus - Clarrisa Marvelianty Thelendra; Ayu Puspitasari; Nella Yantiana (Forum Kerjasama Pendidikan Tinggi, 2025)
This research aims to assess the effect of corporate social responsibility on financial outcomes in IDX-listed mining sector companies and the moderating effect of earnings management and leverage. This study is based on secondary data gathered from annual and sustainability reporting documents covering the years 2021-2023, obtained from the IDX's official platform. A conceptual framework was developed based on legitimacy theory and agency theory, as well as supported by relevant prior studies. To validate the proposed model, moderation analysis was conducted using a combination of financial and non-financial informations. The model of measurement and the structural associations were performed by applying Partial Least Squares Structural Equation Modeling (PLS-SEM) with the WarpPLS software. The results show that CSR has no significant direct effect on financial performance (? = 0.09, p = 0.24). However, earnings management (? = 0.21, p = 0.04) and leverage (? = 0.39, p < 0.01) significantly moderate this relationship. CSR may act as a tool to mitigate reputational risks from earnings management and becomes more effective under high leverage, which pressures managers to use CSR more strategically. These findings support agency theory and highlight the conditional impact of CSR on financial outcomes. CSR may help mitigate risks from earnings management, while leverage encourages more strategic CSR implementation. This study contributes to the literature by providing empirical insights into how CSR affects financial performance in the mining sector, and how this relationship is conditioned by earnings management and leverage.